EMPLOYEE RECRUITMENT AND PLACEMENT PROCESS STRATEGY USING STRENGTH BASED ASSESSMENT - Cuk Jaka Purwanggono (Sosiohumaniora, 2023)
In the face of talent competition, companies compete to attract and retain talented employees to help achieve increasingly stringent organizational goals and a strength-based organization is needed. Performance appraisal cannot be used as a practical improvement tool; Most people may hesitate when a superior assesses performance differently. This research aims to analyze team member recruitment strategies using Strength-Based Assessment. This research method uses a literature review. The data sourced from secondary data, that is, it does not come from direct observation but is the result of research conducted by previous researchers. Data collection came from 20 journals and five books, analyzed according to existing problems. The analytical method is equipped with a description that describes the facts. This research results show that recruitment has a positive impact on business development that adapts to developing business trends, including information technology, and can expand access to information and HR competencies, triggering extraordinary performance with a talent-based approach that prioritizes stories of a person’s potential or strengths (strength-based). The research concludes the need for an evaluation strategy in employee placement and a Strength-Based Assessment evaluation model.